Evaluator competencies in the context of diversity training: The practitioners' point of view. (April 2018) - Froncek, Benjamin; Mazziotta, Agostino; Piper, Verena; Rohmann, Anette
Highlights: This research investigates evaluator competencies within the context of diversity training. A qualitative approach reveals diversity training providers' views of relevant evaluator competencies. The Essential Competencies for Program Evaluators provide a framework for content analysis. Systematic inquiry, reflective practice, and interpersonal competence appear more central than other competencies. Improved communication is recommended in order to better align information needs with requirements of evaluation practice. Abstract: Evaluator competencies have been discussed since the beginnings of program evaluation literature. More recently, the Essential Competencies for Program Evaluators (Ghere et al., 2006; Stevahn, King, Ghere & Minnema, 2005a) have proven to be a useful taxonomy for learning and improving evaluation practice. Evaluation is critical to diversity training activities, and diversity training providers face the challenge of conducting evaluations of their training programs. We explored what competencies are viewed as instrumental to conducting useful evaluations in this specific field of evaluation practice. In an online survey, N = 172 diversity training providers were interviewed via an open answer format about their perceptions of evaluator competencies, with n = 95 diversity training providers contributing statements. The Essential Competencies for Program Evaluators were used to conduct a deductive qualitative content analysis of the statements. While systematic inquiry, reflective practice, and interpersonal competence were well represented, situational analysis and project management were not. Implications are discussed for evaluation capacity building among diversity training providers and for negotiating evaluation projects with evaluation professionals.